UV Sensitivity of Indium-Zinc Oxide Nanofibers - Nadezhda Markova; Olga Berezina; Nikolay Avdeev; Alexander Pergament (Advances in Materials Science and Engineering)
Indium-zinc oxide (IZO) nanofiber matrices are synthesized on SiO2-covered silicon substrates by the electrospinning method. The nanofibers’ dimensions, morphology, and crystalline structure are characterized by scanning electron microscopy, atomic force microscopy, and X-ray diffraction. The results of studying the electrical properties of nanofibers, as well as their sensitivity to UV radiation depending on the In-to-Zn concentration ratio, are presented. It is shown that the highest sensitivity to UV is observed at the indium content of about 50 atomic %. The photocurrent increment with respect to the dark current is more than 4 orders of magnitude. The response and recovery times are 60 and 500 sec, respectively. The results obtained suggest that IZO nanofibers can find application as UV sensors with improved characteristics.